Pembaruan Pendidikan Pesantren Dalam Kerangka Sistem Pendidikan Nasional - Amrizal Amrizal (Sosial Budaya, 2011)
Pesantren is an educational institution in Indonesia. His contribution is felt real to the people of Indonesia began from the beginning of growth until now in the birth of religious scholars or ulema. Actually, goals and curriculum of pesantren that ukhrowi oriented tend considered un-Islamic because it is not in accordance with the values and principles of Islam itself, and is currently rated as a weaknesses of the pesantren word, it will not be able to bring the Indonesian people to survive in the arena life among nations and an increasingly competitive world. Then the reorientation of the objectives and curriculum of pesantren is an inevitable necessity. Goals and curriculum of pesantren that only ukhrowi oriented must be replaced with the goals and curriculum of the integrated ukhrowi-dunyawiyah oriented. That is, goals and curriculum of pesantren should be able to touch all aspects of students as human beings, bot Ruhiyah, jasmaniyah, or 'aqliyah. Thus he will be able to actual his function as' abdullah and khalifatullah well as well.